Estudio de la acción antihiperglucemiante de la rosiglitazona en la intolerancia a la glucosa: fase previa de la diabetes mellitus tipo 2 - Flores Sáenz, José Luis Eduardo (Universidad Autónoma Metropolitana, 2009)
Diabetes mellitus (DM) is a metabolic disease, and a chronic degenerative inflammatory condition characterized by hyperglycemia due to a deficiency in the secretion and/or insulin action that leads to irreversible development of vascular complications. The DM is classified into four categories being the most important type 1 diabetes mellitus (DM1), with idiopathic and autoimmune a etiology, which represents 5 to 10% of cases, and type 2 DM (DM2), due to resistance insulin (RI) occurring in 90 - 95% of patients with DM. The DM2 is the crossroad of globalization and health in the 21st century. Currently, near 246 million people around the world have diabetes with a projected increase of 420 million over the 20 years next. In addition, 200 million people will present impaired glucose tolerance (IGT), a precursor of DM2. In México, 6.5 to 10 million people have DM2, with a prevalence of 10.7% in people between 20 and 69 years. Near two 2 million cases remain undiagnosed. The IGT, an early biochemical changes in DM2, can be detected through a test of oral glucose tolerance test (OGTT). This diagnosis allows taking early therapeutic measures to prevent or at least delay the development of DM2. The objective of this research was to determine if administration of rosiglitazone (RGZ) improves the metabolic status of subjects with IGT, and reduces the risk of developing DM2 and vascular complications. A total of 60 patients with some degree of IGT or pre-diabetes state among workers and students of the Universidad Autónoma Metropolitana-Iztapalapa (UAM-I) were recorded and randomly divided into three groups. In the groups 1 and 2 RGZ (2 mg) or metformin (425 mg) or placebo (425 mg starch) every 12 h were administered quarterly in a cross and double-blind fashion; group 3 received only placebo. At the end of each quarter were given OGTT and insulin curve (IC). Fasting glycated hemoglobin (A1C), total cholesterol, triacylglycerols, HDLcholesterol, creatinine, uric acid, alanine aminotransferase and aspartate aminotransferase (ALT and AST) were determined. Urinalysis, review and update of medical history in relation to their weight, height, body mass index (BMI), waist / hip index, heart rate and blood pressure were performed during or after the end OGTT. The results showed that in group 1 blood glucose curve of glucose tolerance (CGT) with RGZ were significantly lower (P < 0.05), except for minute 180, compared with placebo and metformin. The area under the curve (AUC) and the mean concentration of glucose (MCG) decreased significantly in 19.9% and 19.6% compared to placebo and metformin, respectively. IC showed a significant decrease of insulinemia (P < 0.05), except for minute 0, as well as of AUC, and the mean insulin concentration (MIC). The A1C significantly decreased (9.8%, P < 0.05). Total cholesterol, LDL-cholesterol, VLDL-cholesterol and triglycerides decreased and HDL-cholesterol was increased, in all cases no singnificantly. Creatinine, uric acid, ALT, AST and urinalysis presented no significant changes. For group 2, the CGT with RGZ showed a significant decrease in blood glucose (P < 0.05), except for minute 0. The AUC and MCG were significantly lower by 12.4% and 15.3% compared to placebo and metformin, respectively. The IC showed a significant decrease in insulinemia, except at minute 180. The AUC and MIC significantly decreased in 38.4% and 30.0% compared to placebo and metformin, respectively. The A1C was 5.5 ± 0.08% significantly lower than those obtained with metformin and placebo. Total cholesterol, triacylglycerols and VLDL cholesterol were significantly lower, HDL-cholesterol increased and LDL cholesterol decreased but not significantly. Creatinine, uric acid, ALT, AST and urinalysis presented no significant changes. In placebo group 3 showed no significant change in CTG and most subjects the initial prediabetic state was preserved. The insulinemia of IC, the AUC and the MIC of the third quarter were lower but not statistically significantly different with respect to those of the first two quarters. The A1C was significantly increased (P < 0.05) in the second and third quarter. Similarly, total cholesterol and LDL-cholesterol increased but not significantly, the rest of the biochemical parameters and urinalysis remained without significant changes. We conclude that the administration of RGZ normalized the GCT in subjects with IGT. Otherwise, RGZ decreased the intolerant hyperglycemic peak (IHP), A1C, total cholesterol, triacylglycerols, LDL cholesterol, VLDL and increased HDLcholesterol. Besides, the decrease in insulin resistance elicited by RGZ could reduce the risk of developing DM2 and its vascular complications.; La diabetes mellitus (DM) es una enfermedad metabólica, crónico-degenerativa e inflamatoria que se caracteriza por hiperglucemia debido a una deficiencia de la secreción y/o acción de la insulina que conlleva el desarrollo de complicaciones vasculares irreversibles. La DM se clasifica en cuatro categorías siendo la más relevantes: la DM tipo 1 (DM1) de etiología autoinmune e idiopática, y que se presenta entre el 5 al 10 % de los casos y la DM tipo 2 (DM2) que se debe a una resistencia a la insulina (RI) y se presenta entre el 90 y 95% de los pacientes con DM. La DM2 representa la encrucijada de la globalización y la salud del siglo 21. Actualmente, se estima que 246 millones de personas tienen diabetes y su número se incrementará en el mundo en más de 420 millones en los próximos 20 años. Adicionalmente, 200 millones de personas probablemente presentarán intolerancia a la glucosa (IGT), fase previa de la DM2. En México, la población con DM2 fluctúa entre los 6.5 y 10 millones, con prevalencia de 10.7% en personas entre 20 y 69 años. Se estima que 2 millones de casos de DM2 permanecen sin diagnosticar. La IGT es una de las primeras alteraciones bioquímicas de la DM2 y se detecta a través de una prueba de tolerancia a la glucosa oral (PTGO). El diagnóstico permite adoptar medidas terapéuticas tempranas para prevenir o al menos retrasar el desarrollo de la DM2, lo que podría lograrse con la administración de fármacos, como la rosiglitazona (RZG), que actúan en contra de la resistencia a la insulina. Sin embargo no se cuenta con estudios suficientes en esta dirección. El objetivo de la presente investigación fue determinar si la administración de RGZ mejora el estado metabólico de sujetos con IGT, y disminuye el riesgo del desarrollo de la DM2 y complicaciones vasculares. Se seleccionaron 60 pacientes con algún grado de IGT o estado prediabético entre trabajadores y estudiantes de la Universidad Autónoma Metropolitana-Iztapalapa (UAM-I) y se integraron en tres grupos de forma aleatoria. A los grupos 1 y 2 se les administró trimestralmente, en forma cruzada y doble ciego, RGZ (2 mg) metformina (425 mg), o placebo (425 mg de almidón), cada 12 horas, y al grupo 3 se le administró únicamente placebo. Al final de cada trimestre se les realizó una PTGO de tres horas de duración y al mismo tiempo una curva insulínica (CI), se determinó en ayuno la hemoglobina glicada (A1C), colesterol total, triacilgliceroles, colesterol-HDL, creatinina, ácido úrico, Alanina aminotransferasa y aspartato aminotransferasa (ALT y AST); y durante o al término de la PTGO se realizó urianálisis, revisión y actualización de su historia clínica en relación a su peso, estatura, índice de masa corporal (IMC), índice cintura/cadera, frecuencia cardiaca y tensión arterial.Los resultados del grupo 1 mostraron que las glucemias de la curva de tolerancia a la glucosa (CTG) con RGZ fueron significativamente menores (P < 0.05), excepto para el minuto 180, con respecto al placebo y la metformina. El área bajo la curva (ABC) y la concentración media de glucosa (CMG) disminuyeron significativamente en 19.9% y 19.6% con respecto al placebo y la metformina, respectivamente. Las insulinemias de la CI mostraron un descenso significativo (P < 0.05), excepto para el minuto 0, así como, del ABC y de la concentración media de insulina (CMI). La A1C disminuyó significativamente 9.8%, (P < 0.05). El colesterol total, colesterol-LDL, colesterol-VLDL y triacilgliceroles disminuyeron y el colesterol-HDL se incrementó, pero estos cambios no fueron estadísticamente significativos. La creatinina, ácido úrico, ALT, AST y urianálisis tampoco mostraron cambios significativos. Para el grupo 2, la CTG con RGZ mostró un descenso significativo (P < 0.05) de la glucemia, excepto para el minuto 0. El ABC y la CMG fueron significativamente menores en 12.4% y 15.3% con respecto al placebo y metformina, de manera respectiva. La CI mostró un descenso significativo de la insulinemia, excepto al minuto 180. El ABC y la CMG disminuyeron de manera significativa en 38.4% y 30.0% con respecto al placebo y metformina, de manera respectiva. La A1C fue de 5.5 ± 0.08% significativamente menor que la obtenida con metformina y placebo. Colesterol total, triacilgliceroles y colesterolVLDL fueron significativamente menores, el colesterol-HDL aumentó y el colesterol-LDL disminuyó pero no de manera significativa; creatinina, ácido úrico, ALT y AST y el urianálisis resultaron sin cambios significativos. En el grupo 3, tratado con placebo, las CTG no mostraron cambios significativos y la mayoría de los sujetos conservaron el estado prediabético inicial. Las insulinemias de la CI, el ABC y la CMI del tercer trimestre fueron menores, pero sin diferencia significativa con respecto a los dos primeros trimestres. El A1C se incrementó de manera significativa (P < 0.05) en el segundo y tercer trimestre; de manera semejante, el colesterol total y el colesterol-LDL aumentaron, pero sin significación estadística; el resto de los parámetros bioquímicos y el urianálisis no mostraron cambios significativos. Podemos concluir que la administración de RGZ normaliza la CTG en sujetos con IGT y disminuye el pico hiperglucémico intolerante (PHI), la A1C, el colesterol total, triacilgliceroles, colesterol-LDL y VLDL e incrementa el colesterol-HDL. Además, la RGZ disminuye la resistencia a la insulina por lo que puede reducir el riesgo del desarrollo DM2 y sus complicaciones vasculares.